Better Nutritional Status Is Positively Associated with mRNA Expression of SIRT1 in Community-Dwelling Older Adults in the Toledo Study for Healthy Aging. Issue 9 (31st August 2018) - El Assar, Mariam; Angulo, Javier; Walter, Stefan; Carnicero, José Antonio; García-García, Francisco José; Sánchez-Puelles, José-María; Sánchez-Puelles, Carlos; Rodríguez-Mañas, Leocadio
Abstract: Background: The expression of certain genes involved in response to oxidative stress is likely related to aging-related outcomes, such as frailty in old age. Given nutrition's substantial impact in aging and age-related diseases, one of its mechanisms might be through influencing gene expression. Objective: This study aimed to investigate the association between nutrition and the expression of 15 genes related to cellular response to stress in older community-dwelling individuals. Methods: A nested case-control study of 350 participants (mean ± SEM age: 76.5 ± 6.9 y, 42.9% men, 22% frail according to Fried's criteria) was selected from the Toledo Study for Healthy Aging. Blood-derived RNA was retro-transcribed into complementary DNA. TaqMan Arrays were used for determining gene expression. The Mini Nutritional Assessment (MNA) and the PREDIMED (PREvención con DIeta MEDiterranea) questionnaire measured nutritional status and adherence to the Mediterranean diet (MD), respectively. Data were reweighed so that inference from linear and logistic regression models applied to the original sampling population. Results: Higher MNA scores were associated with higher expressions of the gene coding for sirtuin-1 ( SIRT1 ), regardless of age, sex, and Charlson comorbidity score ( P = 0.04) and even after adjusting for frailty status ( P = 0.016) and level of adherence to the MD ( P = 0.04). Malnutrition risk and SIRT1 gene expression were inversely associated ( P = 0.0045) independently of frailty status ( P = 0.0045) and level of adherence to the MD ( P = 0.0075). Conclusions: In older individuals, improvement in nutritional status is positively associated with SIRT1 gene expression independently of frailty status or adherence to the MD. These findings may provide potential biomarkers and targets for health interventions among the elderly.